Multifunctional nano hydrogel as well as preparation method and application thereof
By developing a multifunctional nanohydrogel, the combination of glutathione modified silk protein, methacrylate pectin and MXene@TiO2 nanosheets is used to achieve dynamic ROS regulation, solving the problems of oxidative stress and tissue regeneration in the treatment of periodontitis, and achieving spatially controlled antibacterial treatment and tissue regeneration effects.
Patent Information
- Application Number
- CN202510236569.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-28
- Publication Date
- 2025-06-03
AI Technical Summary
In the treatment of periodontitis, although acoustic dynamic therapy has antibacterial potential, it has inflammatory responses caused by excessive reactive oxygen species that hinder tissue regeneration. Existing two-dimensional materials such as MXene and TiO2 have limitations in ROS generation and clearance.
A multifunctional nanohydrogel is developed to form a hydrogel with dynamic ROS regulation through the combination of glutathione-modified silk protein, methacrylate pectin and MXene@TiO2 nanosheets, and to achieve space-time controllable antibacterial treatment and tissue regeneration using ultrasound triggering.
The hydrogel can quickly kill bacteria under ultrasound stimulation and remove excess ROS after ultrasound stops, effectively solving the dual challenges of oxidative stress and tissue regeneration, and achieving the dual goals of antibacterial and tissue regeneration.
Smart Images

Figure BDA0005292875320000031 
Figure BDA0005292875320000041 
Figure BDA0005292875320000061
Abstract
Description
Technical Field
[0001] The present application relates to the field of biomedicine, and more specifically, it relates to a multifunctional nano-hydrogel and its preparation method and application. Background Art
[0002] Periodontitis is a chronic inflammatory disease caused by pathogenic microorganisms in subgingival plaque, characterized by progressive destruction of periodontal tissues, including pathological changes such as periodontal inflammation, periodontal pocket formation, and alveolar bone resorption. Sonodynamic therapy (SDT) shows potential in antibacterial aspects, but its application is limited by the inflammatory response caused by excessive reactive oxygen species (ROS), which hinders tissue regeneration. Therefore, it is crucial to develop a new treatment strategy that can effectively manage infection and regulate oxidative stress.
[0003] Two-dimensional materials such as MXene and TiO 2 Show unique advantages in the generation and scavenging of ROS, but have limitations when used alone. Inspired by the symbiotic relationship between rhizobia and leguminous plants, the present invention aims to develop a multifunctional hydrogel with dynamic ROS regulation ability to achieve the dual goals of antibacterial and tissue regeneration. Summary of the Invention
[0004] The invention object of the present application is to develop a multifunctional hydrogel with dynamic ROS regulation ability to achieve the dual goals of antibacterial and tissue regeneration.
[0005] To this end, the present application adopts the following technical solutions:
[0006] In the first aspect, the present application provides a multifunctional nano-hydrogel, and the raw materials used for preparation include glutathione-modified silk fibroin, methacrylated pectin, and MXene@TiO 2 nanosheets.
[0007] Furthermore, the preparation method of the glutathione-modified silk fibroin includes: dissolving natural silk fibroin into a solution using MES buffer, adding EDC and NHS, reacting at room temperature under magnetic stirring, adding reduced glutathione to the above solution, reacting at room temperature under magnetic stirring, dialyzing the reaction solution with deionized water at normal temperature, and freeze-drying to obtain a freeze-dried sample of glutathione-modified silk fibroin.
[0008] Furthermore, the raw material ratios involved in the process are as follows: natural silk fibroin 1-2 g: MES buffer 10-20 mL: NHS 1-2 mg: EDC 1-2 mg: GSH 0.01-0.03 g.
[0009] Furthermore, the preparation method of the methacrylated pectin includes: adding pectin into an MES buffer solution containing NaCl, stirring at room temperature until completely dissolved, adding NHS and EDC, stirring, adding AEMA into the solution, and reacting in the dark at room temperature; adding an excessive amount of acetone to precipitate the solution, drying the obtained polymer under a fume hood, dissolving the obtained polymer in deionized water for purification, dialyzing with deionized water at normal temperature, and freeze-drying to obtain a freeze-dried sample of methacrylated pectin.
[0010] Furthermore, the raw material ratios involved in the process are as follows: 1 - 2 g of pectin: 2 - 3 g of NaCl: 100 - 150 mL of MES buffer solution: 1 - 2 g of NHS: 3 - 4 g of EDC: 1 - 2 g of AEMA.
[0011] Furthermore, the preparation method of the MXene@TiO 2 nanosheets includes: synthesizing monolayer Ti 3 AlC 2 Tx MXene nanosheets by selectively etching the aluminum layer in Ti 3 AlC 2 ; dissolving LiF in concentrated hydrochloric acid, adding Ti 3 AlC 2 powder, stirring for 24 hours, and obtaining neutral pH monolayer Ti 3 AlC 2 Tx MXene nanosheets through ethanol treatment and centrifugal separation.
[0012] In a second aspect, the present application provides a preparation method of the multifunctional nanohydrogel described in the first aspect, including the following steps:
[0013] Copolymerization of GSH-SF and PeMA: adding the GSH-SF solution to TCEP·HCl, stirring, adding the PeMA solution, and inducing with a photosensitizer to form a hydrophobic hydrogel network;
[0014] Introduction of MXene@TiO 2 nanosheets: dispersing MXene@TiO 2 nanosheets in the hydrogel network;
[0015] Curing of the hydrogel: crosslinking the mixture under ultraviolet light irradiation to form a stable hydrogel matrix.
[0016] Furthermore, the photosensitizer is the photoinitiator LAP.
[0017] Furthermore, the methacrylated pectin, glutathione-modified silk fibroin, and photosensitizer are mixed in a volume ratio of 2:1:1.
[0018] In a third aspect, the present application provides the use of the multifunctional nanohydrogel described in the first aspect in the preparation of a drug for treating periodontitis.
[0019] In summary, the present application has the following beneficial effects:
[0020] The present invention proposes a multifunctional MXene@TiO 2 biological heterojunction hydrogel, which realizes spatiotemporally controllable antibacterial therapy and enhanced tissue regeneration through ultrasound-triggered dynamic ROS regulation. This hydrogel can rapidly kill bacteria under ultrasound stimulation and simultaneously scavenge excessive ROS after the ultrasound stops, effectively solving the dual challenges of oxidative stress and tissue regeneration. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Att Figure 1 is a component diagram of the hydrogel.
[0022] Att Figure 2 is an electron micrograph of the hydrogel.
[0023] Att Figure 3 is a nanosheet diameter distribution diagram.
[0024] Att Figure 4 is a nanosheet Zeta potential diagram.
[0025] Att Figure 5 is a hydrogel degradation diagram.
[0026] Att Figure 6 is a hydrogel compressive modulus diagram.
[0027] Att Figure 7 is an evaluation of the proliferation ability of the hydrogel on MC-3T3 cells.
[0028] Att Figure 8 is an evaluation of the cell biocompatibility of the hydrogel.
[0029] Att Figure 9 is an evaluation of the antibacterial ability of the hydrogel against Escherichia coli and Staphylococcus aureus.
[0030] Att Figure 10 is an evaluation of the anti-biofilm ability of the hydrogel against Escherichia coli and Staphylococcus aureus.
[0031] Att Figure 11 is a diagram of the hydrogel promoting periodontal tissue regeneration. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0032] The technical solutions and effects of the present application are further described in detail below with reference to the embodiments. It can be understood that the specific embodiments described herein are only used to explain the present invention, rather than to limit the present invention.
[0033] It should be noted that the materials and methods used in the examples are existing materials and methods unless otherwise specified.
[0034] I. Experimental Materials
[0035]
[0036]
[0037] II. Preparation Examples
[0038] 1. Preparation of Glutathione-Modified Silk Fibroin (GSH-SF)
[0039] Dissolve 1 g of natural silk fibroin in 10 mL of MES buffer to form a solution. Add 1 mg of EDC and 1 mg of NHS, and react at room temperature for 15 minutes under magnetic stirring. Add 0.02 g of reduced glutathione (GSH) to the above solution, and react at room temperature for 15 minutes under magnetic stirring. Dialyze the reaction solution against deionized water at room temperature for 24 h, and obtain a freeze-dried sample of glutathione-modified silk fibroin after freeze-drying.
[0040] In other embodiments, the raw material ratios involved in the process can be arbitrarily selected within the following ranges: natural silk fibroin 1 - 2 g: MES buffer 10 - 20 mL: NHS 1 - 2 mg: EDC 1 - 2 mg: GSH 0.01 - 0.03 g.
[0041] 2. Preparation of Pectin Methacrylate (PeMA)
[0042] Add 1 g of pectin to 100 mL of 2-(N-morpholino)ethanesulfonic acid (MES) buffer containing 2 g of sodium chloride (NaCl), stir at room temperature until completely dissolved, add 1 g of NHS and 3 g of EDC, stir for 10 minutes, add 1 g of AEMA to the solution, and react in the dark at room temperature for 24 hours; add an excess of acetone to precipitate the solution, dry the resulting polymer under a fume hood, dissolve the resulting polymer in deionized water for purification, dialyze against deionized water at room temperature for 72 h, and obtain a freeze-dried sample of pectin methacrylate after freeze-drying.
[0043] In other embodiments, the raw material ratios involved in the process can be arbitrarily selected within the following ranges: pectin 1 - 2 g: NaCl 2 - 3 g: MES buffer 100 - 150 mL: NHS 1 - 2 g: EDC 3 - 4 g: AEMA 1 - 2 g to prepare pectin methacrylate with a high degree of substitution.
[0044] 3. Preparation of Nanosheets (MXene@TiO 2 )
[0045] Preparation of MXene Nanosheets: Monolayer TixMXene nanosheets were synthesized by selectively etching the aluminum layer in Ti3AlC2. 1 g of lithium fluoride (LiF) was dissolved in 20 mL of 9 M concentrated hydrochloric acid, and 5 g of Ti3AlC2 powder was added. After stirring for 24 hours, neutral pH monolayer TixMXene nanosheets were obtained through ethanol treatment and centrifugation. 3 AlC 2 In other embodiments, the raw material ratios involved in the process can be arbitrarily selected within the following ranges: LiF 1 - 2 g: 9 M concentrated hydrochloric acid 20 - 50 mL: Ti3AlC2 powder 5 - 10 g. 3 AlC 2 Preparation of MXene@TiO2: The MXene nanosheets were hydrothermally treated at 180 °C for 12 hours to achieve in-situ growth of TiO2 nanoparticles on the surface of MXene, forming the MXene@TiO2 composite material. 3 AlC 2 4. Preparation of Hydrogel 3 AlC 2 Copolymerization of GSH-SF and PeMA: An 8% (w / v) GSH-SF solution was added to 10 mmol / L tris(2-carboxyethyl)phosphine hydrochloride (TCEP·HCl) and stirred for 15 minutes; then a 4% (w / v) PeMA solution was added, and a hydrogel matrix was formed through photosensitizer induction. A photoinitiator, lithium phenyl(2,4,6-trimethylbenzoyl)phosphate (LAP), was added to the GSH-SF solution as a photosensitizer to promote the coupling reaction between GSH-SF and PeMA, forming a hydrophobic hydrogel network.
[0046] Among them, methacrylated pectin, glutathione-modified silk fibroin, and photoinitiator (LAP) were mixed evenly in a volume ratio of 2:1:1 to obtain a hydrogel prepolymer solution. 3 AlC 2 Introduction of MXene@TiO2 Nanosheets: The MXene@TiO2 nanosheets were dispersed in the hydrogel network (four hydrogels with different concentrations of MXene@TiO2 were formed: SP-0, SP-50, SP-100, and SP-200 hydrogels), as shown in the following table.
[0047] MXene@TiO 2 The MXene@TiO 2 nanosheets were hydrothermally treated at 180 °C for 12 hours to achieve in-situ growth of TiO 2 nanoparticles on the surface of MXene, forming the MXene@TiO
[0048] 4. Preparation of Hydrogel
[0049] Copolymerization of GSH-SF and PeMA: An 8% (w / v) GSH-SF solution was added to 10 mmol / L tris(2-carboxyethyl)phosphine hydrochloride (TCEP·HCl) and stirred for 15 minutes; then a 4% (w / v) PeMA solution was added, and a hydrogel matrix was formed through photosensitizer induction. A photoinitiator, lithium phenyl(2,4,6-trimethylbenzoyl)phosphate (LAP), was added to the GSH-SF solution as a photosensitizer to promote the coupling reaction between GSH-SF and PeMA, forming a hydrophobic hydrogel network.
[0050] Among them, methacrylated pectin, glutathione-modified silk fibroin, and photoinitiator (LAP) were mixed evenly in a volume ratio of 2:1:1 to obtain a hydrogel prepolymer solution.
[0051] MXene@TiO 2 Introduction of MXene@TiO 2 nanosheets: The MXene@TiO 2 nanosheets were dispersed in the hydrogel network (four hydrogels with different concentrations of MXene@TiO
[0052] Sample GSH-SF (wt%) PeMA (wt%) LAP (wt%) <![CDATA[MXene@TiO 2 (ug / ml)]]> SP-0 10 4 2.5 0 SP-50 10 4 2.5 50 SP-100 10 4 2.5 100 SP-200 10 4 2.5 200
[0053] Curing of the hydrogel: The mixture was cross-linked under ultraviolet light irradiation for 20 seconds to form a stable hydrogel matrix, enabling the uniform dispersion of MXene@TiO 2 nanosheets in the hydrogel network, enhancing its mechanical properties and antioxidant activity.
[0054] III. Performance Testing
[0055] 1. Scanning Electron Microscope (SEM)
[0056] Observe the microstructure morphology of the hydrogel and analyze the surface morphology of the freeze-dried hydrogel. The sample was fixed on the SEM stage, adhered with conductive glue, sputtered with platinum for 2 mm in a vacuum coater, and the microscopic morphology of the sample was observed by SEM at an acceleration voltage of 5 kV. At the same time, elemental mapping of the sample surface was performed by Energy Dispersive Spectrum (EDS) carried by SEM at an acceleration voltage of 10 kV.
[0057] Figure 2 Characterization shows that the synthesized hydrogel presents a uniform macroporous structure microscopically, and MXene@TiO 2 is uniformly distributed on the pore walls. The uniform porous interconnected network provides a suitable three-dimensional structure for cell attachment, proliferation, and subsequent tissue healing and regeneration.
[0058] 2. Nano Particle Size and Zeta Potential Analysis
[0059] Evaluate the particle size and Zeta potential of MXene and MXene@TiO 2 nanosheets in ethanol solution. Use the dynamic light scattering (DLS) method to evaluate the particle size and Zeta potential of MXene and MXene@TTiO 2 nanosheets in ethanol solution (0.1 mg / mL).
[0060] Figure 3 It shows that the synthesized MXene and MXene@TiO 2 have particle sizes of 337.7 ± 72.54 nm and 366.6 ± 49.78 nm respectively. Figure 4 It shows that the Zeta potentials of MXene and MXene@TiO 2 are -19.8 mV and -28.0 mV respectively. The lower Zeta potential value of MXene@TiO 2 means that its dispersion system is more stable.
[0061] 3. Degradation Test
[0062] Evaluate the degradation rate of the hydrogel in the collagenase solution. Record the initial weight of the hydrogel as Mi. Place the hydrogel in PBS solution containing 1 μg / mL type I collagenase and incubate at 37 °C. At the corresponding time points, record the weight of the hydrogel Md.
[0063] The formula for calculating the degradation rate is as follows:
[0064]
[0065] Figure 5 It shows that the hydrogel has a low degradation rate within 14 days and maintains certain morphological characteristics.
[0066] 4. Mechanical property test
[0067] Measure the compressive strength and Young's modulus of the hydrogel. Prepare different hydrogel samples using a cylindrical mold (diameter 8 mm × thickness 2 mm) and perform compression tests at a strain rate of 1 mm / min. Calculate the compressive Young's modulus through the slope of the linear region (0 - 20% strain) of the compression strain-stress curve.
[0068] Figure 6 It shows that the higher the addition amount of MXene, the higher the compressive modulus of the composite hydrogel, and SP-200 (with an MXene addition amount of 200 μg / ml) has the highest compressive modulus.
[0069] 5. Cell culture and biocompatibility test
[0070] Cell proliferation and viability test: Evaluate cell proliferation through the CCK-8 kit. Select mouse calvaria pre-osteoblasts MC3T3-E1 (Mouse Calvaria 3T3-E1 pre-osteoblasts) for in vitro experiments. MC3T3-E1 cells are cultured in α-MEM medium supplemented with 10% fetal bovine serum (FBS) and 1% penicillin-streptomycin (P / S) to provide the nutrients required for osteogenic differentiation and proliferation. All cells are cultured in a humidified incubator at 37 °C and 5% CO 2 and the culture medium is changed every 2 - 3 days, and subcultured when the cell density reaches 80 - 90%.
[0071] Set the Ctrl (control) group: Culture cells only using high-glucose α-MEM medium containing 10% fetal bovine serum.
[0072] Set the SP-MXene (experimental) group: Culture cells using conditioned medium. Sterilize 1 mL of freshly prepared hydrogel system under ultraviolet light for 24 hours, soak the hydrogel samples in 20 mL of high-glucose α-MEM medium containing 10% fetal bovine serum, and continuously culture on a shaker at 37 °C for 3 days with a shaking speed of 50 rpm. Collect the supernatant as the conditioned medium for cell culture.
[0073] MC3T3-E1 cells were seeded into 96-well culture plates and cultured overnight with conditioned medium. After 1 and 3 days of culture, they were rinsed 3 times with PBS, 10% CCK-8 detection solution was added, and they were incubated at 37 °C in the dark for 1 h. 100 μL of the supernatant from each well was aspirated into a new 96-well plate, with 3 replicates for each group and a blank control set, and the OD value at 450 nm was detected with an enzyme-linked immunosorbent assay (ELISA) reader.
[0074] Figure 7 The results showed that the hydrogel system did not affect the cell proliferation ability of MC-3T3s and had good biocompatibility.
[0075] Live / dead cell staining experiment: MC-3T3s were seeded in 12-well plates and cultured overnight with conditioned medium, and conditioned medium containing 50 μM H 2 O 2 was added and cultured for 3 days. The live / dead status of the cells was observed using a Calcein-AM / PI double-staining kit. MC3T3-E1s cells were seeded in confocal dishes and cultured overnight with conditioned medium. After 3 days of culture, the original culture medium was discarded, and they were rinsed 3 times with PBS. After diluting the Calcein / PI cell live / dead staining reagent 1000-fold with PBS, it was added to the original well plate and incubated at 37 °C in the dark for 30 minutes. After rinsing 3 times with PBS, they were placed under a laser confocal microscope to observe the fluorescence expression (Calcein corresponded to an excitation light wavelength of 488 nm, and PI corresponded to an excitation light wavelength of 594 nm).
[0076] Figure 8 The results showed that the hydrogel system did not affect the cell viability of MC-3T3s and had good biocompatibility.
[0077] 6. In vitro antibacterial activity evaluation
[0078] CFU counting: To evaluate the antibacterial effect of the hydrogel under different treatment conditions. To evaluate the antibacterial effect of the hydrogel under different treatments, a bacterial dilution experiment was conducted. The hydrogel was immersed in a liquid medium containing a bacterial suspension with a standard concentration of 1×10 6 CFU / mL. The antibacterial activities of E. coli and S. aureus were tested in the following five experimental groups
[0079] (1) PBS group (bacterial suspension without added hydrogel and without ultrasonic treatment);
[0080] (2) SP group (SP hydrogel without MXene@TiO 2 and without ultrasonic treatment);
[0081] (3) SP-MT group (containing MXene@TiO2 and SP hydrogel without ultrasonic treatment);
[0082] (4) SP-US group (without MXene@TiO 2 and SP hydrogel treated with ultrasonic);
[0083] (5) SP-MT-US group (with MXene@TiO 2 and SP hydrogel treated with ultrasonic).
[0084] After co-culturing for 12 hours at 37 °C, the bacterial suspension was collected and serially diluted. Subsequently, the diluted suspension was inoculated onto agar medium. The medium was incubated at 37 °C for 24 hours, and the colony-forming units (CFUs) were counted to evaluate the bacterial survival under different experimental conditions.
[0085] Figure 9 It was shown that the hydrogel of the SP-MT-US group had a strong antibacterial ability, and the antibacterial rates against E. coli and S. aureus were both over 90%.
[0086] 7. Biofilm culture and analysis
[0087] Live / dead staining and confocal laser scanning microscopy (CLSM) analysis: Observe the distribution and thickness of the biofilm. The biofilm was grown on the titanium alloy plate and stained with BacLightTM Bacterial Viability and Counting Kit. After staining, the excess dye was removed by rinsing with PBS, and three-dimensional imaging was performed using a confocal laser scanning microscope (CLSM, Leica, Germany) to observe the distribution and thickness of the biofilm matrix.
[0088] (1) PBS group (bacterial suspension without hydrogel addition and without ultrasonic treatment);
[0089] (2) SP group (without MXene@TiO 2 and SP hydrogel without ultrasonic treatment);
[0090] (3) SP-MT group (with MXene@TiO 2 and SP hydrogel without ultrasonic treatment);
[0091] (4) SP-US group (without MXene@TiO 2 and SP hydrogel treated with ultrasonic);
[0092] (5) SP-MT-US group (with MXene@TiO 2 and SP hydrogel treated with ultrasonic).
[0093] Figure 10It was shown that the hydrogel in the SP-MT-US group had a strong anti-biofilm ability, and the thickness and area of the biofilms formed by E. coli and S. aureus were significantly reduced.
[0094] 8. Periodontitis model evaluation
[0095] Periodontitis model: To evaluate the effect of the hydrogel in the repair of periodontal bone defects. SPF-grade 5-week-old male C57BL / 6J mice provided by the Animal Center of the Ninth People's Hospital of Shanghai were used to establish a periodontitis model. Without damaging the nearby gingival tissue, 5-0 silk threads were ligated around the second maxillary molars (M2) on both sides. At the same time, 20 μL of Porphyromonas gingivalis was injected into the periodontal pockets of M2 to accelerate the induction of inflammation.
[0096] The periodontitis mice were randomly divided into the following five groups, with 6 mice in each group:
[0097] Control group (PBS): The silk threads were removed 14 days after ligation, and PBS buffer was injected into the periodontal pockets of the second maxillary molars on both sides of the mice without ultrasonic treatment.
[0098] SP group: The silk threads were removed 14 days after ligation, and SP hydrogel was injected into the periodontal pockets of the second maxillary molars on both sides of the mice without ultrasonic treatment.
[0099] SP-M: The silk threads were removed 14 days after ligation, and SP-MT hydrogel buffer was injected into the periodontal pockets of the second maxillary molars on both sides of the mice without ultrasonic treatment.
[0100] SP-US group: The silk threads were removed 14 days after ligation, and SP hydrogel was injected into the periodontal pockets of the second maxillary molars on both sides of the mice, and ultrasonic treatment was performed in the first three days (1.5 W / cm 2 , 50% duty cycle, 1 MHz, 4 minutes).
[0101] SP-MT-US group: The silk threads were removed 14 days after ligation, and SP-MT hydrogel buffer was injected into the periodontal pockets of the second maxillary molars on both sides of the mice, and ultrasonic treatment was performed in the first three days (1.5 W / cm 2 , 50% duty cycle, 1 MHz, 4 minutes).
[0102] Fourteen days after the hydrogel treatment, the mice were euthanized, and the maxillary tissue samples were collected for subsequent analysis.
[0103] Micro CT analysis: Evaluation of periodontal bone regeneration. The mice were killed, and the maxilla (including three molars and their surrounding alveolar bone and attached gingival tissue) was collected, fixed in 4% PFA for 72 hours, and scanned at high resolution using Micro-CT. The scanning voltage and current were 50kVp and 200uA, respectively, with an integration time of 338ms and a resolution of 6.0um. Three-dimensional and two-dimensional images were reconstructed using RadiAntDICOM Viewer software. CTAn software was used to analyze and measure the distance between the enamel and alveolar bone apex (CEJ-ABC) between the maxillary first and second molars, the ratio of bone volume to tissue volume (BV / TV), bone mineral density (BMD), the number of trabeculae (Tb.N), and the degree of trabecular separation (Tb.Sp).
[0104] Histological and histomorphometric analysis: Tissue repair was assessed by H&E staining.
[0105] Figure 11 The results showed that the three-dimensional Micro-CT reconstruction images were obtained after sampling from mice. The red arrows indicated the regeneration of alveolar bone. In HE tissue staining, the black arrows indicated the distance between the alveolar bone ridge (CEJ-ABC) and the cementum-enamel junction. The results showed that the injection of the ultrasonically treated SP-MT hydrogel system could promote alveolar bone regeneration.
[0106] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A multifunctional nano-hydrogel, characterized in that: The raw materials used in the preparation include glutathione-modified silk protein, methacrylated pectin and MXene@TiO2 nanosheets.
2. The multifunctional nano-hydrogel according to claim 1, characterized in that: The preparation method of glutathione-modified silk protein comprises: using MES buffer to dissolve natural silk protein into a solution, adding EDC and NHS, reacting at room temperature under magnetic stirring, adding reduced glutathione to the solution, reacting at room temperature under magnetic stirring, dialyzing the reaction solution with deionized water at room temperature, and obtaining a glutathione-modified silk protein freeze-dried sample after freeze-drying.
3. The multifunctional nano-hydrogel according to claim 2, characterized in that: The raw material ratio involved in the process is as follows: natural silk protein 1-2g: MES buffer 10-20mL: NHS1-2mg: EDC 1-2mg: GSH 0.01-0.03g.
4. The multifunctional nano-hydrogel according to claim 1, characterized in that: The preparation method of the methacrylated pectin comprises: adding pectin to a MES buffer solution containing NaCl, stirring at room temperature until the pectin is completely dissolved, adding NHS and EDC, stirring, adding AEMA to the solution, and reacting in a dark place at room temperature; adding an excess of acetone to precipitate the solution, drying the obtained polymer under a fume hood, dissolving the obtained polymer in deionized water for purification, dialyzing with deionized water at room temperature, and freeze-drying to obtain a methacrylated pectin freeze-dried sample.
5. The multifunctional nano-hydrogel according to claim 4, characterized in that: The raw material ratio involved in the process is as follows: pectin 1-2g: NaCl 2-3g: MES buffer 100-150mL: NHS 1-2g: EDC 3-4g: AEMA 1-2g.
6. The multifunctional nano-hydrogel according to claim 1, characterized in that: The preparation method of the MXene@TiO2 nanosheet comprises: synthesizing a single-layer Ti3AlC2 Tx MXene nanosheet by selectively etching the aluminum layer in Ti3AlC2, dissolving LiF in concentrated hydrochloric acid, adding Ti3AlC2 powder, stirring for 24 hours, and obtaining a single-layer Ti3AlC2 Tx MXene nanosheet with a neutral pH by ethanol treatment and centrifugal separation.
7. The method for preparing the multifunctional nano-hydrogel according to any one of claims 1 to 6, characterized in that: The following steps are involved: Copolymerization of GSH-SF and PeMA: Add TCEP·HCl to the GSH-SF solution, stir, add PeMA solution, and add photosensitizer to induce the formation of a hydrophobic hydrogel network; Introduction of MXene@TiO2 nanosheets: Dispersing MXene@TiO2 nanosheets in the hydrogel network; Curing of hydrogel: The mixture is cross-linked under ultraviolet light to form a stable hydrogel matrix.
8. The preparation method according to claim 7, characterized in that: The photosensitizer is a photoinitiator LAP.
9. The preparation method according to claim 7, characterized in that: The methacrylated pectin, glutathione-modified silk protein and photosensitizer are mixed in a volume fraction ratio of 2:1:
1.
10. Use of the multifunctional nano-hydrogel according to any one of claims 1 to 6 in preparing a drug for treating periodontitis.
Citation Information
Cited By
Tooth bleaching material based on biological heterojunction as well as preparation method and application of tooth bleaching material
CN121287549A